Wnt/β-catenin signaling requires interaction of the Dishevelled DEP domain and C terminus with a discontinuous motif in Frizzled. - Tauriello, Daniele V. F.; Jordens, Ingrid; Kirchner, Katharina; Slootstra, Jerry W.; Kruitwagen, Tom; Bouwman, Britta A. M.; Noutsou, Maria; Rudiger, Stefan G. D.; Schwamborn, Klaus; Schambony, Alexandra; Maurice, Madelon M. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Wnt binding to members of the seven-span transmembrane Frizzled (Fz) receptor family controls essential cell fate decisions and tissue polarity during development and in adulthood. The Fz-mediated membrane recruitment of the cytoplasmic effector Dishevelled (Dvl) is a critical step in Wnt/β-catenin signaling initiation, but how Fz and Dvl act together to drive downstream signaling events remains largely undefined. Here, we use an Fz peptide-based microarray to uncover a mechanistically important role of the bipartite Dvl DEP domain and C terminal region (DEP-C) in binding a three-segmented discontinuous motif in Fz. We show that cooperative use of two conserved motifs in the third intracellular loop and the classic C-terminal motif of Fz is required for DEP-C binding and Wnt-induced β-catenin activation in cultured cells and Xenopus embryos. Within the complex, the Dvl DEP domain mainly binds the Fz C-terminal tail, whereas a short region at the Dvl C-terminal end is required to bind the Fz third loop and stabilize the Fz-Dvl interaction. We conclude that Dvl DEP-C binding to Fz is a key event in Wnt-mediated signaling relay to β-catenin. The discontinuous nature of the Fz-Dvl interface may allow for precise regulation of the interaction in the control of Wnt-dependent cellular responses.